Plant root suberin: A layer of defence against biotic and abiotic stresses - Chen, Anle; Liu, Tong; Wang, Zhou; Chen, Xinping (Frontiers in Plant Science, 2022)
Plant roots have important functions, such as acquiring nutrients and water from the surrounding soil and transporting them upwards to the shoots. Simultaneously, they must be able to exclude potentially harmful substances and prevent the entry of pathogens into the roots. The endodermis surrounds the vascular tissues and forms hydrophobic diffusion barriers including Casparian strips and suberin lamella. Suberin in cell walls can be induced by a range of environmental factors and contribute to against biotic and abiotic threats. Tremendous progress has been made in biosynthesis of suberin and its function, but little is known about the effect of its plasticity and distribution on stress tolerance. In field conditions, biotic and abiotic stress can exist at the same time, and little is known about the change of suberization under that condition. This paper update the progress of research related to suberin biosynthesis and its function, and also discuss the change of suberization in plant roots and its role on biotic and abiotic stresses tolerance.